Cultural Crisis During the Pandemic and Its Reflection in Georgian and American Print Media - Tsereteli , Asmat (Pubmedia Social Sciences and Humanities, 2024)
The pandemic became the defining event of early 2020, impacting culture as well as all other areas of life. It emerged as the main architect, artist, director of silence, and dramatist of emptiness. It brought different cities around the world closer together and made them similar with empty streets and a slower pace of life. The pandemic placed new demands on many fields of art; it was a "timeout" for both the world and culture. In some places, art adapted to open spaces, but even in this openness, creative energy remained constrained, and much of what was expressed could not be fully articulated. There were instances where the pandemic became a source of "inspiration" for some artists, prompting them to compose original music, create new works of art, or transition to the online space, finding new ways to use this platform. Covid-19, which suddenly struck the world, drastically changed the global agenda. New regulations were imposed, the usual way of life was disrupted, and the world was unprepared for many of the challenges it faced. Before scientists and researchers could develop effective methods to combat the coronavirus, humanity had already shifted to a remote format. In this paper, we will explore the impact of the pandemic on art and how this period was reflected in print media, using the example of Georgian and American magazines such as "Teatri," "Aril," "Art in America," and "ARTFORUM".